An exploratory study of private companies in Malaysia: critical success factors for enterprise IT risk management - Abdul Hamid, Nor Hasnul Azirah; Husain, Fazlin Marini; Ismail, Najiahtul Syafiqah; Mokhtar, Mazita (UiTM Cawangan Terengganu, Sura Hujung, 23000 Dungun, Terengganu, 2023)
Malaysia’s dynamic economy is characterized by a thriving private sector that heavily relies on information technology (IT) systems and infrastructure to drive operational efficiency, customer engagement, and market competitiveness. However, this reliance exposes organizations to various IT-related risks, including data breaches, system vulnerabilities, and regulatory non-compliance. Consequently, Enterprise IT Risk Management (EITRM) has garnered heightened attention as a proactive strategy to identify, assess, and mitigate potential IT risks that could undermine organizational objectives. Despite the recognition of the critical role of EITRM, a notable gap exists in understanding the specific factors that contribute to its successful implementation within private companies in Malaysia (Said et al., 2020). While several global studies have explored critical success factors (CSFs) in risk management practices (Zhu et al., 2023; Jaeger et al., 2020), there remains a gap in understanding the specific factors that contribute to successful EITRM implementation within the context of private companies in Malaysia.